2009
DOI: 10.1523/jneurosci.3930-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Allosteric Potentiator of the M1Muscarinic Acetylcholine Receptor Increases Activity of Medial Prefrontal Cortical Neurons and Restores Impairments in Reversal Learning

Abstract: M 1 muscarinic acetylcholine receptors (mAChRs) may represent a viable target for treatment of disorders involving impaired cognitive function. However, a major limitation to testing this hypothesis has been a lack of highly selective ligands for individual mAChR subtypes. We now report the rigorous molecular characterization of a novel compound, benzylquinolone carboxylic acid (BQCA), which acts as a potent, highly selective positive allosteric modulator (PAM) of the rat M 1 receptor. This compound does not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
276
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(295 citation statements)
references
References 47 publications
(81 reference statements)
19
276
0
Order By: Relevance
“…Although previous studies indicate that activation of M 1 mAChRs is critical for learning, memory, and executive functions, the role of M 4 mAChRs in modulating cognitive function remains unclear Shirey et al, 2009;Digby et al, 2012;Ma et al, 2009). We found that VU0152100 alone had no effect on PPI or the acquisition of contextual fear conditioning, suggesting that M 4 may not be required for normal hippocampal learning and memory processes in young adult rats.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although previous studies indicate that activation of M 1 mAChRs is critical for learning, memory, and executive functions, the role of M 4 mAChRs in modulating cognitive function remains unclear Shirey et al, 2009;Digby et al, 2012;Ma et al, 2009). We found that VU0152100 alone had no effect on PPI or the acquisition of contextual fear conditioning, suggesting that M 4 may not be required for normal hippocampal learning and memory processes in young adult rats.…”
Section: Discussionmentioning
confidence: 53%
“…However, as the higher doses of amphetamine used in the cognitive studies can induce increases in both dopamine and norepinephrine (McKittrick and Abercrombie 2007), it will be important in future studies to confirm that these effects of VU0152100 are mediated predominately through reversal of dopaminergic signaling. Finally, VU0152100 provides an important M 4 -selective tool compound that used along with recently reported M 1 -selective PAMs (Ma et al, 2009;Shirey et al, 2009) or allosteric agonists (Lebois et al, 2010;Digby et al, 2012) will allow a more complete understanding of the relative roles of these two mAChR subtypes in regulating multiple aspects of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell patch-clamp recordings were performed using coronal slices (300 μm) prepared from 8-9-week-old male C57BL6/J mice (Jackson Laboratories) and a K-gluconatebased intracellular solution as described previously (Shirey et al, 2009). Spontaneous EPSCs were recorded at a holding potential of − 70 mV that is close to the reversal potential of chloride ions; therefore, GABA A receptor-mediated inhibitory currents were undetectable under these conditions.…”
Section: Whole-cell Patch-clamp Recordingsmentioning
confidence: 99%
“…These data are consistent with the hypothesis that changes in mAChR signaling could contribute to the symptoms observed in schizophrenia patients. Of the five mAChR subtypes (M 1 -M 5 ), M 1 is the predominant mAChR subtype expressed in the PFC (Levey et al, 1991) and likely participates in induction of mLTD (Caruana et al, 2011) and other physiological responses that are important for PFC-dependent cognitive functions (Digby et al, 2012;Shirey et al, 2009). We now report discovery and optimization of VU0453595 as a novel, highly selective positive allosteric modulator (PAM) for M 1 that provides excellent pharmacokinetic properties and brain exposure in mice after systemic administration.…”
Section: Introductionmentioning
confidence: 99%
“…Among the muscarinic receptor subtypes (M 1 -M 5 ), much attention has been given to M 1 receptors, because it is implicated in learning and memory processes (Anagnostaras et al, 2003;Shirey et al, 2009). Biochemical studies demonstrated that NDMC exhibits a partial agonist profile at human recombinant M 1 receptors (Davies et al, 2005), which seems to be unique and not shared by any other antipsychotics.…”
Section: Introductionmentioning
confidence: 99%